Penguatan Literasi Dasar melalui Pendampingan Membaca dan Menulis pada Anak Panti Asuhan - Dhari, Putri Wulan; Rusmiati, Rusmiati; Utami, Rizka (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
Literacy skills, particularly reading and writing, are essential foundations for children’s cognitive, academic, and social development. Children living in orphanage often experience limited access to adequate literacy support, leading to disparities in their learning progression. This community program aims to strengthen the literacy abilities of children at the Kasih Ibu Orphanage in Central Aceh through structured mentoring activities. The methods applied include shared reading sessions, guided discussions on text content, writing practice, literacy worksheets, and educational games. Data were collected through observations, children’s worksheets, and activity documentation. The results indicate improvements in reading motivation, active engagement during reading activities, and the development of basic writing skills. Although some children continue to face challenges in reading fluency and text comprehension, the program successfully created an enjoyable learning environment and enhanced their confidence in written communication. Continuous literacy mentoring is expected to further strengthen the children’s foundational literacy skills and contribute positively to their academic growth